Long-term follow-up of long and flat bone eosinophilic granulomas managed only with biopsy - (:unkn) unknown (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: We evaluated long-term clinical and radiological follow-up results of patients with long and flat bone eosinophilic granulomas managed only with biopsy. Methods: Seventeen patients [11 male, 6 female; average age 8.5 years (range: 3.5 to 14 years)] with long and flat bone eosinophilic granulomas were followed after biopsy. Involved bones were femur (5), tibia (3), humerus (2), ulna (1), pelvis (3), scapula (1) and clavicle (1). After confirmation of diagnosis by biopsy, no further surgical intervention was performed. Clinical follow-up was done with preoperative and postoperative MSTS and VAS scores. The healing process was followed with periodic radiographs. Limb-length discrepancy, deformity, and lesion progression or recurrence were recorded. Average follow-up was 65 months (range: 28 to 115 months). Results: Average preoperative MSTS score was 45% (range: 30 to 56.6%), while postoperative 6, 12 and 24 months scores were measured as 76% (range: 70 to 83.3%), 88% (range: 73.3 to 93.3%) and 94% (range: 86.6 to 100%) respectively. Average VAS score, which was 8.4 (range: 6 to 10) preoperatively, had a tendency to decrease postoperatively, and was measured as 3.5 (range: 2 to 5), 2.2 (range: 1 to 3.5) and 1.1 (range: 0 to 2) at 3, 6, and 12 months. Even though the majority of lesions demonstrated complete radiographic healing at 12 months, the healing process extended to 24 months for flat bones. No patients experienced limb-length discrepancy or deformity. All lesions regressed following biopsy and no recurrence was seen. Conclusion: Eosinophilic granuloma has a spontaneous healing potential, and confirming the diagnosis by biopsy is sufficient to obtain good functional and radiological results without any further intervention.
Keywords: Eosinophilic granuloma; langerhans cell histiocytosis; LANGERHANS-CELL HISTIOCYTOSIS; CHILDREN; LESIONS; SYSTEM